1996
DOI: 10.1002/etc.5620150702
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical interactions affecting hepatic trace element levels in aquatic birds

Abstract: Abstract-Knowledge of elemental interactions is important to the toxicological assessment of wildlife in the geochemical environment. This study determines the concentrations of Al, As, B, Ba, Be, Cd, Cr, Cu, Fe, Pb, Li, Mg, Mn, Hg, Mo, Ni, Se, Ag, V, and Zn in aquatic bird liver, fish liver, whole bivalves, insects, and waters in several aquatic ecosystems in northern California. There is evidence of strong in vivo and environmental interactions, including the observation of manganese as a possible cofactor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 38 publications
0
3
1
Order By: Relevance
“…Trace elements are often correlated [57,58]. In contrast to the clustering among cadmium, manganese, selenium, mercury, and arsenic found in surf scoters ( Melanitta perspicil‐lata ) in San Francisco Bay [57] and between mercury and selenium in surf scoters and greater scaup ( Aythya marila ) [58] from San Francisco Bay, we found that cadmium correlated with only selenium and arsenic but not with mercury or manganese. Mercury did not correlate with any metal in livers of lesser scaup from western Lake Erie nor did mercury correlate with any other trace element in white‐winged scoters from Alaska [38].…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Trace elements are often correlated [57,58]. In contrast to the clustering among cadmium, manganese, selenium, mercury, and arsenic found in surf scoters ( Melanitta perspicil‐lata ) in San Francisco Bay [57] and between mercury and selenium in surf scoters and greater scaup ( Aythya marila ) [58] from San Francisco Bay, we found that cadmium correlated with only selenium and arsenic but not with mercury or manganese. Mercury did not correlate with any metal in livers of lesser scaup from western Lake Erie nor did mercury correlate with any other trace element in white‐winged scoters from Alaska [38].…”
Section: Discussioncontrasting
confidence: 88%
“…These values were well below levels associated with zinc toxicosis (1,200 μg/g dry wt [56]). Copper was somewhat higher in livers of scaup from Lake Erie and Indiana Harbor (means 59.9 μg/g dry wt) than those of scaup from the Chesapeake Bay (mean 40 μg/g wt) but were lower than several other waterfowl species collected from Chesapeake Bay [43,48] and were within the normal range [57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1), one explanation might be that the level of Hg is too high for the self‐protection mechanism. Additionally, it has been reported that Se also detoxifies other heavy metals [29,30,38–40], and toxic metals (e.g., Cd and Mn) and metalloid (e.g., As) may compete for binding with Se‐protein and weaken the correlation between Hg and Se. The exact cause, however, remains to be investigated further.…”
Section: Resultsmentioning
confidence: 99%